Kajian Implementasi Desain Universal Pada Taman Samarendah - Noviana, Mafazah; Hidayati, Zakiah (Universitas Sebelas Maret Surakarta, 2020)
City Parks in terms of social functions can be used as a place for social interaction, a means for sports, play and recreation. As a public facility, city parks must accommodate all groups of people, ranging from normal people, children, disabled people and the elderly. One way to provide facilities for all visitors is to apply universal design principles. Universal design aims to facilitate everyone's life through the creation of products, the built environment and communication to be used by as many people as possible and provide added value for everyone. The purpose of this study is to examine the implementation of universal design principles in Taman Samarendah.The location of the study was in Taman Samarendah, using a descriptive qualitative research method. Seven principles of universal design and Permen PUPR No.14/PRT/2017 becomes the guideline and standardization in this study. The results of this study indicate that Samarendah Park has not fully applied the universal design principles and accessibility standards. The most universal principles of design that are not applied are the principle of tolerance for error and the principle of low physical effort. The principle that is most widely applied is the size and space for approach.